Selenium in Human Health and Gut Microflora: Bioavailability of Selenocompounds and Relationship With Diseases - Ferreira, Rannapaula Lawrynhuk Urbano; Sena-Evangelista, Karine Cavalcanti Maurício; de Azevedo, Eduardo Pereira; Pinheiro, Francisco Irochima; Cobucci, Ricardo Ney; Pedrosa, Lucia Fatima Campos (Frontiers in Nutrition, 2021)
This review covers current knowledge of selenium in the dietary intake, its bioavailability, metabolism, functions, biomarkers, supplementation and toxicity, as well as its relationship with diseases and gut microbiota specifically on the symbiotic relationship between gut microflora and selenium status. Selenium is essential for the maintenance of the immune system, conversion of thyroid hormones, protection against the harmful action of heavy metals and xenobiotics as well as for the reduction of the risk of chronic diseases. Selenium is able to balance the microbial flora avoiding health damage associated with dysbiosis. Experimental studies have shown that inorganic and organic selenocompounds are metabolized to selenomethionine and incorporated by bacteria from the gut microflora, therefore highlighting their role in improving the bioavailability of selenocompounds. Dietary selenium can affect the gut microbial colonization, which in turn influences the host's selenium status and expression of selenoproteoma. Selenium deficiency may result in a phenotype of gut microbiota that is more susceptible to cancer, thyroid dysfunctions, inflammatory bowel disease and cardiovascular disorders. Although the host and gut microbiota benefit each other from their symbiotic relationship, they may become competitors if the supply of micronutrients is limited. Intestinal bacteria can remove selenium from the host resulting in two to three times lower levels of host’s selenoproteins under selenium-limiting conditions. There are still gaps in whether these consequences are unfavorable to humans and animals or whether the daily intake of selenium is also adapted to meet the needs of the bacteria.